The Students’ Use of Google Classroom in Learning English - Salam, Urai (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
This study investigates the students’ use of Google Classroom in English language learning. The data were derived from Likert Scale questionnaires including open-ended questions distributed to 119 English Education students. There were five aspects covered in the questionnaire: access to Google Classroom, perceived usefulness, communication and interaction, instructional delivery and students’ satisfaction. Meanwhile, open-ended inquired students’ real experiences. The result showed the mean score with the following distribution: 4,49 for easy access to GC, 3,93 for perceived usefulness, 3,63 for communication and interaction, 4,10 for instructional delivery, and 3,82 for students’ satisfaction. Some students shared their experiences in using Google Classroom. Some of them said that Google Classroom brought their courses to their face so that they can participate and continue work on their classes beyond the working hours. Even many of them still worked and uploaded their assignments till midnight. In spite of these positive findings, the study revealed that some students fell into serious addiction to social media technology.